Visa em Debate 2021
DOI: 10.22239/2317-269x.01458
|View full text |Cite
|
Sign up to set email alerts
|

Análise da rotulagem de bebidas mistas de frutas e vegetais denominadas detox

Abstract: Introdução:Os rótulos fornecem informações para a orientação do consumidor sobre as escolhas alimentares mais adequadas às suas necessidades, sendo um importante canal de comunicação entre o consumidor e o produtor de alimentos. Para cumprir esse papel, é fundamental que essas estejam corretas e atendam aos parâmetros legais estabelecidos. Objetivo:Avaliar a conformidade dos rótulos das bebidas mistas industrializadas à base de frutas e vegetais que apresentavam a denominação suco detox, comercializadas em Bel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
0
0
Order By: Relevance
“…Yet, a local study carried out by Prado et al 26 analyzed the labels of 70 samples of RTE-MPV sold in the city of Ribeirao Preto, SP, and found that most of them fall short on the lack of information about the place of origin (country) (91.4%) and absence of complete address (82.9%). Other studies that evaluated the label of different foods also found lack of information about list of ingredients, nutritional content, and expiration date 15,27,28 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, a local study carried out by Prado et al 26 analyzed the labels of 70 samples of RTE-MPV sold in the city of Ribeirao Preto, SP, and found that most of them fall short on the lack of information about the place of origin (country) (91.4%) and absence of complete address (82.9%). Other studies that evaluated the label of different foods also found lack of information about list of ingredients, nutritional content, and expiration date 15,27,28 .…”
Section: Resultsmentioning
confidence: 99%
“…In Brazil, as in other countries, food packaged in the absence of consumers must be labeled 9 . Food labeling is an important instrument of communication between the producer and consumers and must contain reliable and consistent information, including food composition, nutritional content, country of origin and storage conditions, among others, allowing consumers to be aware of their choices, purchases and/or what they consume 10,11,12,13,14,15,16 . Nevertheless, certain food categories have exemptions.…”
Section: Introductionmentioning
confidence: 99%
“…Além disso, este achado vai de encontro a resultados de outros estudos que encontraram inconformidades na rotulagem de produtos alimentícios brasileiros em relação às legislações vigentes [23][24][25][26] . Silva et al 10 , por exemplo, avaliaram a rotulagem de sete bebidas mistas de frutas e vegetais denominadas detox e, em 100% das amostras, foi observado irregularidade do uso da referida alegação, além da ausência do registro no MAPA. Ainda, segundo os autores, 70% das amostras analisadas apresentaram irregularidades na lista de ingredientes e informação nutricional e 57% não apresentaram o conteúdo líquido na forma correta.…”
Section: /13unclassified
“…A busca pelo termo "bebidas detox" no Google, por exemplo, totaliza em mais de vinte milhões de resultados. Ainda, estudo realizado por Silva et al 10 , entre os anos de 2017 e 2019, encontraram, apenas no mercado de Belo Horizonte, 23 bebidas industrializadas à base de frutas e vegetais com a denominação detox.…”
Section: Introductionunclassified